O Terço dos Homens Mãe Rainha (THMR) e a experiência pastoral na base da Igreja. - Lima, Luiz Henrique Gregório de (2022)
Contemporary times challenge us to undertake new ways of proposing the faith, through evangelization and mission. Several inviting perspectives emerge, such as the Rosary of Men, which uses a popular expression that is so old and eminently feminine to bring the masculine closer to the base of the Church. This proposal was presented in such a compelling and mobilizing way that it motivated the Brazilian Catholic Church to designate a Bishop to closely monitor this growing expression of faith. Even with all its attributes, an attentive pastoral look is opportune, with the aim of making better use of this expression, as well as avoiding possible deviations, narrowness and/or closure, sometimes resulting from the influences of the cultural context that was created, still avoiding make it anachronistic and ambiguous. It is opportune to rid ourselves of naivety and seek to treat this manifestation of faith with common sense, for its better pastoral use within the Church, understanding that there are several initiatives of groups of Men's Rosaries in Brazil. This work deals specifically with the Rosary of Men Mother Queen (THMR), linked to the popular representation of the Apostolic Movement of Schoenstatt. Based on bibliographical research related to the theme, a methodological course was built that is divided into moments: the first one seeks to make a historical rescue of the devotion to Mary and the Rosary, as well as the origin of the THMR; in a second that presents a theological analysis of the Marian devotion translated in devotion to the Rosary, in the perspective of the new evangelization, from the popular piety and a third that enters in the challenges of the urban pastoral and seeks to design, in a propositional way, possible paths for a better use of this expression in the community.